Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Decoupled active in-row following strategy for collaborative tobacco-harvesting robots based on ultra-wideband localization and visual perception - Rui Su; Juan Li; Cheng Liu; Ling Wang; Lei Gao; Delun Li; Du Chen (Computers and Electronics in Agriculture, 2026)

High-precision semantic segmentation of apple internal diseases based on CT imaging and deep learning - Linfeng Su; Zhanling Hu; Ziqi Li; Jiacheng Sun; Juan Zhao (Postharvest Biology and Technology, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Thermally interfered nonlinearity of vibro-acoustically modulated interfacial waves in bolted connection for early detection of preload loosening - Jianbin Li; Juan Jin; Yi He; Qian Li; Zhen Zhang; Zhongqing Su (Engineering Structures, 2026)

Brown carbon optical emissions from residential coal combustion in china: Dominance of solvent-insoluble components - Fan Li; Qiaoqiao Wang; Nan Ma; Zechao Hu; Xiaocong Zhao; Ning Yang; Zheng Yang; Guangjin Liu; Yuanwei Zhong; Jiangchuan Tao; Juan Hong; Yaqing Zhou; et al. (Atmospheric Research, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

LncRNA MNX1-AS1 drives the progression of non-small cell lung cancer and serves as a ceRNA to target COMMD8 by sponging miR-218-5p - Gao-Feng Liu; Li Zhou; Yu-Bo Zhao; Jia-Hong Tang; Qing-Yuan Li; Xiao-Yong Ding; Xiao-Zhen Zhang; Su-Juan Cui; Yong Zhang; Zhen-Wei Sun (Journal of Molecular Histology, 2026)
The role and mechanistic action of MNX1-AS1 in non-small cell lung cancer (NSCLC) remain unclear. This study aimed to investigate the function of MNX1-AS1 in the progression of NSCLC. A total of 40 paired tumor and adjacent lung tissue samples from patients with NSCLC were collected to investigate the expression of MNX1-AS1. H1299 and HCC827 cells were transfected with sh-MNX1-AS1, shRNA-NC, miR-218-5p mimic, mimic-NC, pcDNA3.1-COMMD8, or empty vector (pcDNA3.1). The expression of MNX1-AS1, miR-218-5p, and COMMD8 was detected using quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated using CCK-8 assays, while cell migration and invasion were evaluated using Transwell assays. Dual-luciferase reporter and RNA pull-down assays were performed to validate the targeting interactions between MNX1-AS1 and miR-218-5p, as well as between COMMD8 and miR-218-5p. In vivo, a nude mouse model was established: tumor volume and weight were measured after four weeks. Gene expression in tumor tissue was quantified using qRT-PCR, and Ki-67 expression was evaluated using immunohistochemistry. MNX1-AS1 expression was significantly upregulated in NSCLC tissues ( P < 0.05) and was correlated with poor prognosis in NSCLC patients. MNX1-AS1 knockdown markedly suppressed the viability, migration, and invasion of H1299 and HCC827 cells ( P < 0.05). Mechanistically, MNX1-AS1 acted as a molecular sponge for miR-218-5p, thereby relieving miR-218-5p-mediated repression of its direct target COMMD8 ( P < 0.05). Functional rescue experiments revealed that miR-218-5p silencing or COMMD8 overexpression partially reversed the inhibitory effects of MNX1-AS1 knockdown on the cell viability, migration, and invasion of H1299 and HCC827 cells. In vivo, sh-MNX1-AS1 significantly reduced tumor volume and weight ( P < 0.05). Moreover, the expression of MNX1-AS1, COMMD8, and Ki-67 were downregulated, while the expression of miR-218-5p was upregulated in sh-MNX1-AS1 tumor tissues ( P < 0.05). MNX1-AS1 promotes the progression of NSCLC by modulating the miR-218-5p/COMMD8 axis.

High-performance quantum interconnect between bosonic modules beyond transmission loss constraints - Hongwei Huang; Jie Zhou; Weizhou Cai; Weiting Wang; Yilong Zhou; Yunlai Zhu; Ziyue Hua; Yifang Xu; Lida Sun; Juan Song; Tang Su; Ming Li; et al. (Science Bulletin, 2026)

A BRIGHT platform advances integrated hazard indexing toward actionable control of human pathogenic bacteria in residential buildings - Qisheng Li; Huan Liu; Ling N. Jin; Lumeng Liu; Hua Zhou; Wenmao Zeng; Yingxian Zhai; Tian Chen; Jinyan Yu; Dongdong Su; Juan Lin; Qian Wang; et al. (Building and Environment, 2026)

The dual role of DNA methylation inhibitor 5-azacytidine in postharvest peach fruit quality and disease resistance - Ziwen Su; Shenge Li; Shaolei Guo; Juan Yan; Zhixiang Cai; Mingliang Yu; Zhijun Shen; Jianlan Xu (Postharvest Biology and Technology, 2026)

Hepatoprotective and anti-inflammatory dibenzocyclooctadiene lignans from fruits of Kadsura coccinea - Guy Paulin M. Kemayou; Juan-jiang Wu; Wen-chao Zhou; Shi-qi Liu; Piao-piao Jiang; Hanwen Yuan; Wei Su; Bin Li; Simeon F. Kouam; Wei Wang; Yu-pei Yang (Phytochemistry Letters, 2026)

Magnesium isotope geochemistry in continental flood basalts: implications for mantle source heterogeneity - Sakine Moradi; Lie-Meng Chen; Peter C. Lightfoot; Kang-Jun Huang; Qiao Su; Song-Yue Yu; Li-Juan Zhu; Rui-Zhong Hu (Geochimica et Cosmochimica Acta, 2026)

Sequential bacterial-fungal fermentation upgrades Juncus effusus into an antibacterial biosorbent for cationic dyes - Hai-Juan Zhao; Su Sun; Zhen-Yu Wang; Li Chen; Muhammad Wajid Ullah; Yan-Bo Zhang; Jian-Gang Zhou (Biomass and Bioenergy, 2026)

Attenuation of antibiotics and endocrine disruptors flux along the Land-To-Sea continuum: Dominant role of terrestrial ecosystems and remediation potential of salt marsh ecosystems - Zi-Long Mo; Yi-Qin Chen; Yang Yu; Ling-Kan Su; Juan-Ying Li (Marine Pollution Bulletin, 2026)

Contrasting land-use sources of microplastic and endocrine-disrupting compound pollution in a major coastal river network - Weimin Yao; Juan-Ying Li; Bangping Deng; Jie Yin; Jingxi Li; Jiawei Kang; Xin Wang; Nicholas J. Craig; Lei Su (Marine Pollution Bulletin, 2026)

Dietary creatine supplementation promoted growth performance, muscle growth and protein deposition in red swamp crayfish (Procambarus clarkii) fed with all-plant-protein diets - Xinyuan Li; Changchun Song; Shouqi Xie; Min Wan; Yangyang Liu; Chenxi Wang; Guogen Su; Feng Huang; Juan Tian (Aquaculture, 2026)

Critical windows and joint effects of prenatal heat and relative humidity exposure on stillbirth: A prospective longitudinal cohort study - Zhan Li; Yuxin Bi; Shuangying Li; Shaofei Su; Lebing Wang; Juan Li; Shuanghua Xie; Enjie Zhang; Minhui Hu; Shaowen Wu; Jianhui Liu; Chenghong Yin; et al. (Environmental Research, 2026)

Drivers of microplastic accumulation in urban agricultural soils: A data-driven source apportionment of plastic mulch and mixed land use - Lei Su; Jiawei Kang; Weimin Yao; Nicholas J. Craig; Maria Pogojeva; Juan-Ying Li (Journal of Hazardous Materials, 2026)

Thermal degradation kinetics and behavior of MPN from Ginkgo biloba - Yu Kong; Yi-yuan Zhou; Ya-ping Wang; Xiao-fang Wang; Shan Duan; Mo-wen Su; Juan Zhao; Li-min Wang; Qing Kang; Xin-jun Du (Journal of Food Engineering, 2026)

Impact of soil compaction and seasonal freeze-thaw cycles on the microstructural evolution and aggregate stability of Mollisol - Boxiang Zhang; Bo Liu; Shuang Li; Juan Fu; Yanfeng Jia; Haoming Fan; Chengjiu Guo; Fangli Su; Renming Ma (Soil and Tillage Research, 2026)

Controls on heavy metal variability in a coastal mountainous river: Impacts of tides, typhoons, and anthropogenic activities - Yalong Li; Ni Su; Yun Zhao; Ergang Lian; Chao Li; Juan Xu; Ping Yin; Shouye Yang (Journal of Geochemical Exploration, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Microplastic and phthalate ester contamination in aquaculture: Source contributions and the benefits of eco-friendly farming - Juan-Ying Li; Xiaocheng Kang; Weimin Yao; Nicholas J. Craig; Lei Su (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Deep Subdomain Adaptation Network for Three-Dimensional Mineral Prospectivity Modeling with Imbalanced Data: A Case Study of the Damiao–Hongshila Fe–V–Ti Belt, China - Zhiqiang Zhang; Wenliang Chen; Emmanuel John M. Carranza; Wei Han; Xinxing Liu; Yingjie Li; Juan Zhang; Feng Li; Ziyang Lu; Yongjun Su; Gongwen Wang (Natural Resources Research, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Resistance mechanisms and fitness outcomes of tetraniliprole, one novel diamide insecticide, in a near-isogenic strain of Spodoptera litura (Lepidoptera: Noctuidae) - Peng Lu; Ren Li; Xiao Guo; Juan Tang; Yilu Tong; Shengran Zhang; Qi Su; Cheng Qu; Ran Wang (Pesticide Biochemistry and Physiology, 2026)

The centennial legacy of disturbances on sedimentation and carbon burial in an estuarine mangrove ecosystem, South China - Juan Su; Yaobei Lin; Penghui Li; Zhangcai Qin; Luhua Xie; Fan Wang; Weiguang Li; Jinghong Zhang (Journal of Oceanology and Limnology, 2026)

Evaluation of the lipolytic and antioxidant activities of different strains of coagulase-negative staphylococci in fermented sausages - Dan Li; Yuyu Du; Liya Su; Yaqiu Lin; Jiong Zheng; Fidel Toldrá; Chenglin Zhu; Muying Du; Yuan Liu; Juan Chen (Meat Science, 2025)

Phage-conjugated chlorin e6: A strategy overcoming phage resistance in biofilm eradication and wound infection therapy of carbapenem-resistant Acinetobacter baumannii - Jianhui Su; Siyi Chen; Zhishen Huang; Haoxuan He; Huanhuan Zou; Xiaoyi Huang; Yongzhao Xie; Hongxia Zhao; Zhenbo Xu; Tao Lei; Juan Li; Haiyan Zeng (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microfluidic engineering of AgNPs@ZIF-8 composites enables tunable peroxidase-like catalytic activity for enhanced bacterial inactivation - Chong Hu; Juan Tao; Liqiang Zhang; Jiancheng Zha; Panpan Cui; Yanbao Li; Yuan Zhou; Jing Su; Feng Liu; Liangjun Li (Chemical Engineering Journal, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Full-genome sequence of a novel potyvirus infecting Sauropus androgynus - Li-Juan Zhu; Shulian Su; Jingke Li; Yubin Chi; Yankun Zhu; Xing Chen; Lan-Yi Su; Juncheng Zhang; Zhongtian Xu (Virus Genes, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Iron isotope variability in the suspended load across the Changjiang (Yangtze) River basin: The tally of source and weathering contributions - Zhiwei He; Ana Cristina Vasquez; Junjie Guo; Ni Su; Juan Xu; Dongyong Li; Simon V. Hohl; Shouye Yang (Global and Planetary Change, 2025)

Smartphone-integrated multi-emission Eu-MOF hydrogel for visual, discrimination of antibiotics in milk and honey - Wenxi Zhang; Xinyuan Zhang; Jing Sun; Yanjie Lv; Xiao Li; Juan Hou; Zhongmin Su (Food Chemistry, 2025)

Biocontrol mechanism of a newly isolated Streptomyces sp. JL2001 against Ralstonia solanacearum via aerugine - Zixian Zeng; Wei Cao; Hong Pu; Dousheng Wu; Sai Jiang; Meng Su; Yajing Wang; Zhi Wang; Xin Zhao; Juan Li; Shunxiang Li; Lin Jiang (Pesticide Biochemistry and Physiology, 2025)

Magnetically boosted light-driven hydrogel microrobots for ultrasensitive and fast detection of PFOS distribution in unprocessed urine, bile, and whole blood - Xinmeng Wang; Yanwen Liu; Su Li; Weiyan Wang; Juan Wang (Journal of Hazardous Materials, 2025)

The Impact of Biochar Combined with Submerged Plants on the Storage and Stability of Rhizospheric Soil Organic Carbon in Wetlands - Yang Yu; Sheng-Nan Du; Bang-Ping Deng; Ling-Kan Su; Juan-Ying Li (Wetlands, 2025)

A self-powered photocatalytic fuel sensor for single-cell analysis with high reliability - Kejun Guo; Lin Zhong; Su Li; Xiya Liu; Junjie He; Linjing Liu; Juan Wang (Chemical Engineering Journal, 2025)

Bromine radicals and hydroxyl radicals efficiently degrade emerging organic contaminants in the UVA photolysis of bromine process - Tao Yang; Xiujuan Kong; Ge Zeng; Maoju Jiang; Linqian An; Peng Su; Qixiao Lv; Jun Ma; Juan Li (Journal of Environmental Chemical Engineering, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

Investigating factors influencing residents’ willingness to pay for marine litter management: the role of value-belief-norm theory - Zhihua Xu; Yingjie Li; Hongyan Su; Juan Xu (Journal of Coastal Conservation, 2025)

Compositional complexity of heterogeneous impact glasses in lunar soils: significance and pitfalls - Qian W. L. Zhang; Bin Su; Pierre Lanari; Jia-Hui Liu; Jia-Long Hao; Yu Liu; Liu-Yang Chen; Di Zhang; Jiang-Yan Yuan; Juan Wang; Xian-Hua Li; Qiu-Li Li (Contributions to Mineralogy and Petrology, 2025)
Heterogeneous impact glass beads are abundant in lunar soils and have been extensively used to study the geological processes that shaped the Moon’s surface. In this study, we examine the compositional complexity of three heterogeneous glass beads containing undigested zirconolite and zircon, using EPMA, Nano-SIMS mapping, and SIMS U–Pb isotope analyses. The undigested zircon and zirconolite crystals document three key volcanic events in the lunar history: at ~ 4.31 Ga the formation of alkali-suite rocks from the highlands, and at ~ 3.92 Ga, and ~ 2.04 Ga mare basalts, indicating that the U–Pb system in these zirconium-bearing crystals remains undisturbed during the ultra-high-temperature, short-duration impact melting events. EPMA and Nano-SIMS mapping reveal significant compositional inhomogeneity in the glass matrices, which complicates accurate provenance determination based on in-situ analysis. Bulk composition calculated from quantitative maps, however, provides a more reliable reference for inferring the origins of these beads. The high proportions of common Pb in the heterogeneous glass matrices, originating from diffusion-controlled processes during partial melting of impact involved minerals, introduce substantial uncertainties in U–Pb dating, complicating the interpretation of impact event ages. These findings highlight the challenges of U–Pb dating in heterogeneous glass beads and provide new insights into the preservation of pristine age information in lunar impact materials.

Solid-state fermentation of rapeseed meal using Schizochytrium ATCC 20888 to improve docosahexaenoic acid and degradate toxin - Hongmei Deng; Xinyi Jian; Lihuan Li; Qian Zhou; Yi Pu; Furong Wang; Juan Zeng; Yanqiu Su (Food Bioscience, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Characterization of the complete genome of a novel allexivirus infecting Sauropus androgynus in China - Li-Juan Zhu; Lan-Yi Su; Xing Chen; Shifang Pan; Fagang Xia; Yan-Hong Han; Zhongtian Xu; Qian Xu (Archives of Virology, 2025)

Sildenafil citrate induces prostatic hyperplasia in BPH model rats and aged rats - Sisi Huang; Dongyan Huang; Xin Su; Rongfu Yang; Congcong Shao; Juan Jiang; Jun Li; Jianhui Wu (Toxicology and Applied Pharmacology, 2024)

Facile synthesis of geopolymer-based hierarchical porous materials for efficient adsorption-photocatalysis of dye wastewater - Han Xiao Su; Chan Juan Li; Yao Jun Zhang (Journal of Environmental Chemical Engineering, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Maternal Serum Iodine Concentrations in Early Pregnancy Exhibited Well Diagnostic Ability for Thyroid Dysfunction, Inverse Associations with Gestational Weight Gain, and Birth Size: Longitudinal Analyses Based on Huizhou Mother-Infant Cohort - Zhao-min Liu; Huan-huan Long; Dan Li; Ai-ping Fang; Chao-gang Chen; Cheng Wang; Min-min Li; Yi Wu; Su-juan Zhang; Wen-jing Pan (Biological Trace Element Research, 2024)

Cadmium and pyrene in the soil modify the properties of earthworm-mediated soil - Zhiming Shi; Jie Yan; Run Su; Shuyu Shi; Wenwen Li; Yonghua Zhao; Juan Zhang; Congying Wang (Science of The Total Environment, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Acacetin targets STING to alleviate the destabilization of the medial meniscus-induced osteoarthritis in mice - Dingjun Xu; Linjie Zhang; Chenyu Song; Dinglei Zhang; Chunlei Xing; Juan Lv; Huihui Bian; Minyu Zhu; Minxuan Han; Yongsheng Yu; Li Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Segmentation of beach plastic fragments’ contours based on self-organizing map and multi-shape descriptors: A rapid indication of fragmentation and wearing types - Lei Su; Xinyue Dong; Junjie Peng; Hong Cheng; Nicholas J. Craig; Bo Hu; Juan-Ying Li (Journal of Hazardous Materials, 2024)

Phase inversion of bigels tuned by the concentration of soy protein isolate in the binary hydrogel matrix - Ling-Zhi Su; Ying-Xin Chen; Shi-Qi Zhang; Chun Hu; Jun-Bo He; Wei-Nong Zhang; Li-Juan Han (Food Hydrocolloids, 2024)

High-risk ARGs (HRA) Chip: A high-throughput qPCR-based array for assessment of high-risk ARGs from the environment - Huan-Qin Li; Mei-Rong Xu; Xin-Li An; Hu Liao; Li-Juan Li; Wei Li; Jian-Qiang Su (Water Research, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Matching periodate peak absorbance by far UVC at 222 nm promotes the degradation of micropollutants and energy efficiency - Tao Yang; Ge Zeng; Maoju Jiang; Peng Su; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Juan Li (Journal of Hazardous Materials, 2024)

A Fe(III)-driven strategy for efficient closed-loop recovery of critical metals from spent LiNi Co Mn O powder - Fanyun Su; Xiangyang Zhou; Yingkang Liu; Zhenxiao Li; Huaishuo Kou; Xiaojian Liu; Haikun Xu; Jingjing Tang; Yanxi Chen; Guangli Liu; Hui Wang; Juan Yang (Chemical Engineering Journal, 2024)

Microplastics in different tissues of historical and live samples of endangered mega-fish (Acipenser sinensis) and their potential relevance to exposure pathways - Yueping Zheng; Sirui Huang; Houyong Fan; Hanqi Liu; Jianan Xu; Nicholas J. Craig; Juan-Ying Li; Wenhui He; Lei Su (Aquatic Toxicology, 2024)

Mechanisms and clinical landscape of N6-methyladenosine (m6A) RNA modification in gastrointestinal tract cancers - Dan-Hua Zhu; Kun-Kai Su; Xiao-Xi Ou-Yang; Yan-Hong Zhang; Xiao-Peng Yu; Zu-Hong Li; Seyedeh-Sara Ahmadi-Nishaboori; Lan-Juan Li (Molecular and Cellular Biochemistry, 2024)
Epigenetics encompasses reversible and heritable chemical modifications of non-nuclear DNA sequences, including DNA and RNA methylation, histone modifications, non-coding RNA modifications, and chromatin rearrangements. In addition to well-studied DNA and histone methylation, RNA methylation has emerged as a hot topic in biological sciences over the past decade. N6-methyladenosine (m6A) is the most common and abundant modification in eukaryotic mRNA, affecting all RNA stages, including transcription, translation, and degradation. Advances in high-throughput sequencing technologies made it feasible to identify the chemical basis and biological functions of m6A RNA. Dysregulation of m6A levels and associated modifying proteins can both inhibit and promote cancer, highlighting the importance of the tumor microenvironment in diverse biological processes. Gastrointestinal tract cancers, including gastric, colorectal, and pancreatic cancers, are among the most common and deadly malignancies in humans. Growing evidence suggests a close association between m6A levels and the progression of gastrointestinal tumors. Global m6A modification levels are substantially modified in gastrointestinal tumor tissues and cell lines compared to healthy tissues and cells, possibly influencing various biological behaviors such as tumor cell proliferation, invasion, metastasis, and drug resistance. Exploring the diagnostic and therapeutic potential of m6A-related proteins is critical from a clinical standpoint. Developing more specific and effective m6A modulators offers new options for treating these tumors and deeper insights into gastrointestinal tract cancers.

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Reference Intervals of Serum Iodine Concentration in Chinese Pregnant Women - Yi Wu; Huan-huan Long; Su-juan Zhang; Min-Min Li; Chao-gang Chen; Cheng Wang; Zheng-yu Sheng; Yan-bin Ye; Shu-yu Zuo; Wen-jing Pan; Zhao-min Liu (Biological Trace Element Research, 2024)

Antihypertensive treatment during pregnancy induces long-term changes in gut microbiota and the behaviors of the attention deficit hyperactivity disorder offspring - Hong-Bao Li; Meng-Lu Xu; Wen-Jie Xia; Yuan-Yuan Dong; Bo Peng; Qing Su; Xiao-Min Wang; Jia-Yue Yu; Ya-Nan Gao; Jun-Zhe Wu; Meng-Yue Xu; Jin-Bao Yang; et al. (Toxicology and Applied Pharmacology, 2024)

Ferrocene-functionalized zirconium-oxo clusters for achieving high-performance thermocatalytic redox reactions - Su-Juan Yao; Jiao-Min Lin; Long-Zhang Dong; Ying-Lin Li; Ning Li; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Lactate ameliorates palmitate-induced impairment of differentiative capacity in C2C12 cells through the activation of voltage-gated calcium channels - Juan Wan; Chunfang Cheng; Xiaonuo Li; Yuanjie Zhu; Hu Su; Yanchun Gong; Kaizhi Ding; Xiaofei Gao; Caixia Dang; Guoyin Li; Wei Jiang; Li-Hua Yao (Journal of Physiology and Biochemistry, 2024)

Lactate induces C2C12 myoblasts differentiation by mediating ROS/p38 MAPK signalling pathway - Chunfang Cheng; Wenxi Li; Yuanqian Ye; Yuanjie Zhu; Mengyuan Tang; Zhihong Hu; Hu Su; Caixia Dang; Juan Wan; Zhibin Liu; Yanchun Gong; Li-Hua Yao (Tissue and Cell, 2024)

The association between per-/polyfluoroalkyl substances in serum and thyroid function parameters: A cross-sectional study on teenagers living near a Chinese fluorochemical industrial plant - Lin-Na Xie; Xiao-Chen Wang; Li-Qin Su; Sai-Sai Ji; Wen Gu; Holly Barrett; Xiao-Jie Dong; Hui-Juan Zhu; Sha-Sha Hou; Zhen-Huan Li; Yi-Lin Liu; Ling Zhang; et al. (Science of The Total Environment, 2024)

Eudesmane sesquiterpenoids with inhibitory effects on NO production from Artemisia princeps - Hong-Xia Li; Ning Diao; Ya-Jie Hu; Su-Juan Wang; Dong Liang; Gui-Jie Zhang (Phytochemistry, 2024)

Arsenic disturbs neural tube closure involving AMPK/PKB-mTORC1-mediated autophagy in mice - Xiujuan Li; Gexuan Li; Shuo Cui; Yue Hou; Zelin Li; Ziyi Yan; Tingjuan Huang; Taoran Zhao; Hongkai Su; Bingrui Zhou; Juan Zhang; Ruifang Ao; et al. (Food and Chemical Toxicology, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Generation of •OH and intermediate manganese species for the efficient removal of micropollutants via photocatalysis of permanganate by indium oxide - Juan Li; Maoju Jiang; Peng Su; Qixiao Lv; Linqian An; Ge Zeng; Xiangyang Hou; Wenqi Li; Chunzhao Chen; Jun Ma; Tao Yang (Chemical Engineering Journal, 2024)

Application of controlled-release urea increases maize N uptake, environmental benefits and economic returns via optimizing temporal and spatial distributions of soil mineral N - Mingxue SUN; Juan LI; Lili ZHANG; Xiaomeng SU; Ning LIU; Xiaori HAN; Songjiang WU; Zhentao SUN; Xiangdong YANG (Pedosphere, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Identifying the drivers of chlorophyll-a dynamics in a landscape lake recharged by reclaimed water using interpretable machine learning - Chenchen Wang; Juan Liu; Chunsheng Qiu; Xiao Su; Ning Ma; Jing Li; Shaopo Wang; Shen Qu (Science of The Total Environment, 2024)

Interactions between microplastics and insects in terrestrial ecosystems—A systematic review and meta-analysis - Juan-Ying Li; Yang Yu; Nicholas J. Craig; Wenhui He; Lei Su (Journal of Hazardous Materials, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

Curcumin alleviates AFB1-induced nephrotoxicity in ducks: regulating mitochondrial oxidative stress, ferritinophagy, and ferroptosis - Haiyan Liu; Ying He; Xinglin Gao; Tong Li; Baoxin Qiao; Lixuan Tang; Juan Lan; Qian Su; Zhiyan Ruan; Zhaoxin Tang; Lianmei Hu (Mycotoxin Research, 2023)

Quantitative analysis of TCE biodegradation pathway in landfill cover utilizing continuous monitoring, droplet digital PCR and multi-omics sequencing technology - Zhilin Xing; Shangjie Chen; Fuqing Xu; Xia Su; Fang Gou; Yunchun Shi; Hao Chen; Jinxin Xiang; Juan Li; Tiantao Zhao (Journal of Environmental Management, 2023)

Exploring HONO formation and its role in driving secondary pollutants formation during winter in the North China Plain - Shaobin Zhang; Guo Li; Nan Ma; Yao He; Shaowen Zhu; Xihao Pan; Wenlin Dong; Yanyan Zhang; Qingwei Luo; Jeannine Ditas; Uwe Kuhn; Yuxuan Zhang; et al. (Journal of Environmental Sciences, 2023)

Berberine attenuates uric acid-induced cell injury by inhibiting NLRP3 signaling pathway in HK-2 cells - Jingna Zheng; Shiting Gong; Gong Wu; Xiaohong Zheng; Jincan Li; Juan Nie; Yanlu Liu; Baoyi Chen; Yuhong Liu; Ziren Su; Jiannan Chen; Yucui Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Hyperuricemia (HUA) is a common chronic metabolic disease that can cause renal failure and even death in severe cases. Berberine (BBR) is an isoquinoline alkaloid derived from Phellodendri Cortex with strong antioxidant, anti-inflammatory, and anti-apoptotic properties. The purpose of this study was to investigate the protective effects of berberine (BBR) against uric acid (UA)-induced HK-2 cells and unravel their regulatory potential mechanisms. The CCK8 assay was carried out to detect cell viability. The expression levels of inflammatory factors interleukin-1β (IL-1β) and interleukin-18 (IL-18) and Lactate dehydrogenase (LDH) were measured using Enzyme-linked immunosorbent assays (ELISA). The expression of the apoptosis-related protein (cleaved-Caspase3, cleaved-Caspase9, BAX, BCL-2) was detected by western blot. The effects of BBR on the activities of the NOD-like receptor family pyrin domain containing 3 (NLRP3) and the expression of the downstream genes were determined by RT-PCR and western blot in HK-2 cells. From the data, BBR significantly reversed the up-regulation of inflammatory factors (IL-1β, IL-18) and LDH. Furthermore, BBR down-regulated protein expression of pro-apoptotic proteins BAX, cleaved caspase3 (cl-Caspase3), cleaved caspase9 (cl-Caspase9), and enhanced the expression of antiapoptotic protein BCL-2. Simultaneously, BBR inhibited the activated NLPR3 and reduced the mRNA levels of NLRP3, Caspase1, IL-18, and IL-1β. Also, BBR attenuated the expression of NLRP3 pathway-related proteins (NLRP3, ASC, Caspase1, cleaved-Caspase1, IL-18, IL-1β, and GSDMD). Furthermore, specific NLRP3-siRNA efficiently blocked UA-induced the level of inflammatory factors (IL-1β, IL-18) and LDH and further inhibited activated NLRP3 pathway. Collectively, our results suggested that BBR can alleviate cell injury induced by UA. The underlying unctionary mechanism may be through the NLRP3 signaling pathway.

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Monitoring of insecticide resistance for Apolygus lucorum populations in the apple orchard in China - Xueli Wang; Heng Su; Juan Wang; Guoping Li; Hongqiang Feng; Jinyong Zhang (Crop Protection, 2023)

High mechanical CuO@stainless steel mesh for continuous and durable separation of surfactant-stabilized viscous and light/heavy-mixed oily emulsions in liter-scale - Qing He; Meiling Guo; Juan Shu; Hua Hu; Hongwei Su; Guilong Yan; Zhenyu Li; Li Wang; Dong Xiang; Chunxia Zhao; Yuanpeng Wu; Wei Wang; et al. (Journal of Water Process Engineering, 2023)

One-step leaching mechanism for total elemental recovery from spent lithium-ion batteries utilizing ethylene diamine tetraacetic acid - Fanyun Su; Qi Meng; Xiangyang Zhou; Xiaojian Liu; Juan Yang; Jingjing Tang; Wan Yang; Penghui Cao; Zhenxiao Li; Hui Wang; Yayun Ma (Journal of Environmental Chemical Engineering, 2023)

A sandwiched photoelectrochemical sensor for high-throughput single-cell analysis based on low-toxic and near-infrared AgInS2 microarray - Lin Zhong; Kejun Guo; Su Li; Juan Wang (Chemical Engineering Journal, 2023)

Irisin Attenuates Apoptosis Following Ischemia–Reperfusion Injury Through Improved Mitochondria Dynamics and ROS Suppression Mediated Through the PI3K/Akt/mTOR Axis - Ji-fei Liu; Gang Su; Li-xia Chen; Juan-ping Zhou; Juan Gao; Jia-jia Zhang; Qiong-hui Wu; Wei Chen; De-yi Chen; Zhen-chang Zhang (Molecular Neurobiology, 2023)

Analysis of polyhalogenated carbazoles and two related compounds in earthworms using a modified QuEChERS method with GC/MS and GC/MS/MS - Chaojie Li; Qi Su; Juan Wu; Xinmei Zhou; Dan Zhong; Xincheng Liu; Shanshan Zhou (Environmental Science and Pollution Research, 2023)

Characteristics, sources and health risks of organotin compounds in marine organisms from the seas adjacent to the eastern ports of China - Sheng-Nan Shu; Rui-Tong Jiang; Jie Yin; Qian Wang; Lei Su; Nicholas J. Craig; Juan-Ying Li (Regional Studies in Marine Science, 2023)

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

Atmospheric radioactive nuclide deposition on the coast of the Maowei Sea, northern Beibu Gulf, China - Xilong Wang; Jiaodi Zhou; Kaijun Su; Jinzhou Du; Longtao Wei; Xing Li; Juan Du; Dongliang Lu (Frontiers in Marine Science, 2023)
The natural radioisotopes 7 Be, 210 Pb, and 210 Po, with different half-lives, are all particle-reactive and serve as natural tracers to study sources and transportation of sediments, sedimentation rates, and sediment chronology. Atmospheric deposition of these radioisotopes is the premise and foundation of their tracing application. The Maowei Sea is a semi-closed bay along the Beibu Gulf, which is an important gulf in the northwest of the South China Sea, but the atmospheric deposition of the abovementioned radioisotopes has not been systematically reported along the coast. In this research paper, the atmospheric depositional fluxes of 7 Be, 210 Pb, and 210 Po were observed over a period from June 2018 to December 2021 on the coast of the Maowei Sea. The annual atmospheric depositional fluxes (Bq m -2 yr -1 ) of 7 Be, 210 Pb, and 210 Po on the coast of the Maowei Sea were 496.80, 201.72, and 58.08, respectively. The distributions for 7 Be and 210 Pb depositional fluxes during a whole year (years 2019 and 2021) followed a bimodal pattern, with one peak from February to April and another peak from August to October, while the distribution for 210 Po depositional flux showed only one peak during the year of 2019 and another during 2021. The deposition flux and activity of 7 Be showed a strong positive correlation with the deposition flux and activity of 210 Pb, respectively; the deposition flux and activity of 210 Po also showed positive correlations with the deposition fluxes and activities of 210 Pb and 7 Be, respectively, indicating a similarly scavenging behavior from the atmosphere. A Pearson correlation matrix was used to illustrate the factors influencing the atmospheric depositions and found that precipitation, air quality index (AQI), and PM (both PM 2.5 and PM 10 ) were the major factors that influenced the deposition of these three radionuclides. Precipitation had significant positive correlations with the deposition fluxes of all three radionuclides, indicating that, for these radionuclides, rainfall was the main scavenging way from the atmosphere. The observations for specific single rainfall events and their air mass backward trajectory analyses showed that the air masses movement during the rainfall may be another important factor that impacted the depositional fluxes for 7 Be, 210 Pb, and 210 Po.

Removal of iodide anions in water by silver nanoparticles supported on polystyrene anion exchanger - Li Li; Su-Juan Yu; Rong-Gang Zheng; Peng Li; Qing-Cun Li; Jing-Fu Liu (Journal of Environmental Sciences, 2023)

Synergistic effects of vegetation and microorganisms on enhancing of biodegradation of landfill gas - Chen Shangjie; Wang Yongqiong; Xu Fuqing; Xing Zhilin; Zhang Xiaoping; Su Xia; Li Juan; Zhao Tiantao; Wan Shibin (Environmental Research, 2023)

Accumulation and re-distribution of microplastics via aquatic plants and macroalgae - A review of field studies - Sirui Huang; Ruitong Jiang; Nicholas J. Craig; Hua Deng; Wenhui He; Juan-Ying Li; Lei Su (Marine Environmental Research, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

CircMAN1A2 contributes to nasopharyngeal carcinoma progression via enhancing the ubiquitination of ATMIN through miR-135a-3p/UBR5 axis - Qian-Qian Dang; Pei-Hong Li; Juan Wang; Jing-Yi Zhao; Su-Nan Zhai; Ying-Juan Zheng; Dao-Ke Yang (Human Cell, 2023)

Recovery of valuable metals from spent lithium-ion batteries by complexation-assisted ammonia leaching from reductive roasting residue - Fanyun Su; Xiangyang Zhou; Xiaojian Liu; Juan Yang; Jingjing Tang; Wan Yang; Zhenxiao Li; Hui Wang; Yaguang Zhang; Yayun Ma (Chemosphere, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

One-step selective separation and efficient recovery of valuable metals from mixed spent lithium batteries in the phosphoric acid system - Xiangyang Zhou; Wan Yang; Xiaojian Liu; Jingjing Tang; Fanyun Su; Zhenxiao Li; Juan Yang; Yayun Ma (Waste Management, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Heterojunction engineering of Ni3S2/NiS nanowire for electrochemical hydrogen evolution - Meng Chen; Qing Su; Nutthaphak Kitiphatpiboon; Juan Zhang; Changrui Feng; Shasha Li; Qiang Zhao; Abuliti Abudula; Yufei Ma; Guoqing Guan (Fuel, 2023)

Efficient recovery of valuable metals from spent Lithium-ion batteries by pyrite method with hydrometallurgy process - Fanyun Su; Xiangyang Zhou; Xiaojian Liu; Juan Yang; Jingjing Tang; Wan Yang; Zhenxiao Li; Hui Wang; Yayun Ma (Chemical Engineering Journal, 2023)

Selective extraction of lithium from spent LiNixCoyMnzO2 cathode via in-situ conversion of ethylene glycol in subcritical water system - Yayun Ma; Xiaojian Liu; Xiangyang Zhou; Yuehui He; Jingjing Tang; Fanyun Su; Wan Yang; Sicheng Fan; Jiong Wang; Zhenxiao Li; Juan Yang (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis - Long Liu; Feng-Ming Yan; Chen-Chen Zhao; Li-Juan Su; Qiu-Ying Huang; Qing-Bo Tang (Journal of Pest Science, 2023)
Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1 , drive social immunity in insect colonies is still unknown. Here, we used a ‘host–pathogen’ system (host: Reticulitermes chinensis ; pathogen: Metarhizium anisopliae ) to explore the impact of miRNAs on social immunity in termite colonies. We found that RNAi-mediated silencing of Dicer-1 led to decreased miRNA concentration, significantly inhibited carbohydrate and energy metabolism and affected other life processes, such as the immune response and oxidation–reduction reactions, in whole body of the termite. In behavioural defence, silencing Dicer-1 significantly diminished defensive social behaviours such as locomotion, grooming, cannibalism and burial in termite groups when encountering fungal contamination. In physiological defence, Dicer-1 silencing and miR-71-5 stimulation resulted in significantly decreased antifungal activities of termites. Furthermore, both Dicer-1 -silenced and miR-71-5 stimulant-treated termite groups exhibited a high level of mortality during fungal contamination. Our findings demonstrated the important role of miRNAs in shaping social immunity in termite colonies, providing insights necessary to understand the potential mechanisms underlying behavioural and physiological disease defences in insects and hence laying the groundwork for miRNA-based pest control.

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Genome-wide Identification and Characterization of the Strawberry (Fragaria Vesca) FvAP2/ERF Gene Family in Abiotic Stress - Yanli Su; Zonghuan Ma; Juan Mao; Wenfang Li; Xuejing Cao; Baihong Chen (Plant Molecular Biology Reporter, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Promising application of polyoxometalates in the treatment of cancer, infectious diseases and Alzheimer’s disease - Xuechen Wang; Shengnan Wei; Chao Zhao; Xin Li; Jin Jin; Xuening Shi; Zhenyue Su; Juan Li; Juan Wang (JBIC Journal of Biological Inorganic Chemistry, 2022)

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Stereumamides E-H, four new minor quaternary ammonium hybrids from Stereum hirsutum - Qian-Yi Hu; Yuan-Chang Duan; Xue-Juan Pu; Su-Su Li; Guo-Hong Li; Pei-Ji Zhao (Natural Product Research, 2022)

Estimating submarine groundwater discharge at a subtropical river estuary along the Beibu Gulf, China - Xilong Wang; Kaijun Su; Juan Du; Linwei Li; Yanling Lao; Guizhen Ning; Li Bin (Acta Oceanologica Sinica, 2021)

Shattering-resistance of an elite soybean variety ‘Heihe 43’ and identification of shattering-resistant genes - Dezhi Han; Jianan Han; Siqi Jiang; Bohong Su; Bo Zhang; Zhangxiong Liu; Hongrui Yan; Li-Juan Qiu (Euphytica, 2021)

Exogenous ABA and its inhibitor regulate flower bud induction of apple cv. ‘Nagafu No. 2′ grafted on different rootstocks - Wen-Fang Li; Juan Mao; Jing Su; Xin-Wen Li; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Trees, 2021)

Resveratrol-induced apoptosis is associated with regulating the miR-492/CD147 pathway in malignant melanoma cells - Shuang Zhao; Ling Tang; Wangqing Chen; Juan Su; Fangfang Li; Xiang Chen; Lisha Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Impacts of native vegetation on the hydraulic properties of the concentrated flows in bank gullies - Zheng-an Su; Zhou-yao He; Tao Zhou; Jun-jie Wang; Xiao-yi Wang; Li-juan Wang; Hai-dong Fang; Liang-tao Shi; Yi-han Liu; Zuo Wu (Journal of Mountain Science, 2021)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Effects of CEPA and 1-MCP on Flower Bud Differentiation of Apple cv. ‘Nagafu No.2’ Grafted on Different Rootstocks - Wen-Fang Li; Juan Mao; Xin-Wen Li; Jing Su; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Journal of Plant Growth Regulation, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Gene-based SNP identification and validation in soybean using next-generation transcriptome sequencing - Yong Guo; Bohong Su; Junyong Tang; Fulai Zhou; Li-Juan Qiu (Molecular Genetics and Genomics, 2018)

Different Hippocampus Functional Connectivity Patterns in Healthy Young Adults with Mutations of APP/Presenilin-1/2 and APOEε4 - Li Juan Zheng; Yun Yan Su; Yun Fei Wang; U. Joseph Schoepf; Akos Varga-Szemes; Jonathan Pannell; Xue Liang; Gang Zheng; Guang Ming Lu; Gui Fen Yang; Long Jiang Zhang (Molecular Neurobiology, 2018)

NCAM affects directional lamellipodia formation of BMSCs via β1 integrin signal-mediated cofilin activity - Jia-Jia Bi; Jing Li; Bin-Feng Cheng; Hai-Jie Yang; Qiong-Qiong Ding; Rui-Fei Wang; Su-Juan Chen; Zhi-Wei Feng (Molecular and Cellular Biochemistry, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

A new macrolactin antibiotic from deep sea-derived bacteria Bacillus subtilis B5 - Wei Li; Xi-Xiang Tang; Xia Yan; Zhen Wu; Zhi-Wei Yi; Mei-Juan Fang; Xin Su; Ying-Kun Qiu (Natural Product Research, 2016)

The dopamine beta-hydroxylase gene polymorphism rs1611114 is associated with schizophrenia in the Chinese Zhuang but not Chinese Han population - Jianxiong Long; Guifeng Huang; Baoyun Liang; Weijun Ling; Xiaojing Guo; Juan Jiang; Li Su (Molecular Genetics and Genomics, 2016)

Downregulation of Glutamate Transporter EAAT4 by Conditional Knockout of Rheb1 in Cerebellar Purkinje Cells - Nan-Wei Jiang; De-Juan Wang; Ya-Jun Xie; Liang Zhou; Li-Da Su; Huashun Li; Qin-Wen Wang; Ying Shen (The Cerebellum, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

New cytotoxic and anti-inflammatory compounds isolated from Morus alba L. - Jing Qin; Min Fan; Juan He; Xing-De Wu; Li-Yan Peng; Jia Su; Xiao Cheng; Yan Li; Ling-Mei Kong; Rong-Tao Li; Qin-Shi Zhao (Natural Product Research, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Polycyclic aromatic hydrocarbons in the largest deepwater port of East China Sea: impact of port construction and operation - Juan-Ying Li; Yu Cui; Lei Su; Yiqin Chen; Ling Jin (Environmental Science and Pollution Research, 2015)

Transdifferentiation of bone marrow-derived mesenchymal stem cells into salivary gland-like cells using a novel culture method - Liang Liang; Jun Wang; Yuming Zhang; Zhiyuan Shen; Jun Zheng; Jianhu Li; Zhongping Su; Juan Cai; Wei Jiang; Moyi Sun (Biotechnology Letters, 2015)

Geissoschizine methyl ether N -oxide, a new alkaloid with antiacetylcholinesterase activity from Uncaria rhynchophylla - Wei-Wei Jiang; Jia Su; Xing-De Wu; Juan He; Li-Yan Peng; Xiao Cheng; Qin-Shi Zhao (Natural Product Research, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Response of vacuolar processing enzyme in Malus hupehensis and MhVPEγ-overexpressing Arabidopsis to high temperature stress - Qian Su; Kun Ran; Xiu-Jin Men; Wei-Wei Zhang; Shu-Lei Fan; Li-Juan Yan; Hong-Qiang Yang (Acta Physiologiae Plantarum, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

One new alkaloid from Chelidonium majus L. - Wen-Juan Zhang; Chun-Xue You; Cheng-Fang Wang; Li Fan; Ying Wang; Yang Su; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2014)

Uric formaldehyde levels are negatively correlated with cognitive abilities in healthy older adults - Jing Yu; Tao Su; Ting Zhou; Yingge He; Jing Lu; Juan Li; Rongqiao He (Neuroscience Bulletin, 2014)

Ovalbumin enhances YKL-40, IL-5, GM-CSF, and eotaxin expression simultaneously in primarily cultured mouse tracheal epithelial cells - Su-qin Ben; Ya-li Qiu; Juan Zhou; Xiao-yu Zhou; Shan Zhang; Yi Wu; Shao-qing Ju; Song-shi Ni (In Vitro Cellular & Developmental Biology - Animal, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Erratum to: Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Retrograde cPLA2α/Arachidonic Acid/2-AG Signaling Is Essential for Cerebellar Depolarization-Induced Suppression of Excitation and Long-Term Potentiation - Li-Da Su; De-Juan Wang; Dong Yang; Ying Shen; Ying-Hong Hu (The Cerebellum, 2013)

Novel mutation c.980_983delATTA compound with c.986C>A mutation of the FRMD7 gene in a Chinese family with X-linked idiopathic congenital nystagmus - Feng-wei Song; Bin-bin Chen; Zhao-hui Sun; Li-ping Wu; Su-juan Zhao; Qi Miao; Xia-jing Tang (Journal of Zhejiang University-SCIENCE B, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

The respiratory burst activity and expression of catalase in white shrimp, Litopenaeus vannamei, during long-term exposure to pH stress - Wei-Na Wang; Bao-Sheng Li; Jin-Jian Liu; Lei Shi; M. J. Alam; Shi-Juan Su; Juan Wu; Lei Wang; An-Li Wang (Ecotoxicology, 2012)

Loss-of-function mutations in filaggrin gene associate with psoriasis vulgaris in Chinese population - Zhengmao Hu; Zhimin Xiong; Xiaojuan Xu; Fangfang Li; Lina Lu; Wei Li; Juan Su; Yalan Liu; Deyuan Liu; Zhiguo Xie; Yu Peng; Yehong Kuang; et al. (Human Genetics, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

Identification and expression of a putative LPS-induced TNF-α factor from Asiatic hard clam Meretrix meretrix - Hong-jun Li; Qing Yang; Xiang-gang Gao; Hao Su; Juan Wang; Chong-bo He (Molecular Biology Reports, 2012)

Inhibition of hepatitis C virus replication by single and dual small interfering RNA using an HCV-infected cell model - Xiao-kang Xing; Su-juan Li; Ji-liang He; Zhi Chen (Biotechnology Letters, 2012)

A miRNA-492 binding-site polymorphism in BSG (basigin) confers risk to psoriasis in Central South Chinese population - Li-Sha Wu; Fang-Fang Li; Liang-Dan Sun; Dai Li; Juan Su; Ye-Hong Kuang; Gang Chen; Xiao-Ping Chen; Xiang Chen (Human Genetics, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Ching-Chyuan Su; Juan-Yu Chang; Tung-Cheng Li; Shuan-Yow Li (Human Genetics, 2010)

SSR and SCAR mapping of a multiple-allele male-sterile gene in Chinese cabbage (Brassica rapa L.) - Hui Feng; Peng Wei; Zhong-Yun Piao; Zhi-Yong Liu; Cheng-Yu Li; Yu-Gang Wang; Rui-Qin Ji; Shu-Juan Ji; Ting Zou; Su-Ryun Choi; Yong-Pyo Lim (Theoretical and Applied Genetics, 2009)

Flavonoids from Daphne giraldii Nitsche - Juan Su; Zhijun Wu; Yunheng Shen; Runhui Liu; Chuan Zhang; Huiliang Li; Weidong Zhang (Natural Product Research, 2008)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

Characterization of a cDNA coding for an extracellular calmodulin-binding protein from suspension-cultured cells of Angelica dahurica - Guo-Hong Mao; Li-Xia Hou; Cun-Bao Ding; Su-Juan Cui; Da-Ye Sun (Planta, 2005)